THE EFFECT OF EDUCATION, COURSES AND TRAINING ON THE PROFESSIONALISM OF NAVAL OFFICERS - Rakam Rakam; Pramono Sigit; Anton Nugroho (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2022)
The development of the Indonesian Navy's strength is carried out through a strategic planning process manifested in four activity programs, namely (1) the Marine Readiness Support Program (2) Modernization Program for Alutsista and Non-Alutsista as well as the Development of Facilities and Infrastructure for the National Defense for Marine (3) Professionalism Enhancement Program for Marine Personnel (4) Marine Management and Operation Implementation Program. The Indonesian Navy realizes that the main strength of all force-building programs lies in the quality of the human resources (HR) possessed by the Indonesian Navy. However, the existing reality reveals various kinds of problems and obstacles that hinder the process of improving the quality of existing human resources. For this reason, the Indonesian Navy seeks to improve the pattern of training for personnel by issuing policies that spur the performance of the personnel development system within the Indonesian Navy. From these problems, a research or modeling is needed that can represent how the influence of the Indonesian Naval Personnel Development Pattern and Indonesian Navy Policy on Officer Professionalism to create superior navy personnel in line with the Indonesian Navy development program towards the World Maritime Axis. The method used in this study uses SPSS (Statistical Package for the Social Sciences) in looking for modeling and by carrying out a questionnaire to determine the percentage of assessments regarding the effect of education on performance in the service. The results showed that there was a significant direct influence between the variables of the Navy's policy on personnel development, especially the education system. In addition, there is an indirect influence between the Navy's policy on professionalism through personnel development as a mediating variable. Keywords: Indonesian Naval Policy, Personnel Development, Education System , SPSS